Intervenciones de enfermería para pacientes en postoperatorio inmediato de amigdalectomía, revisión sistemática - Tamami Caspi, Gissela Raquel (2026)
Introduction: Tonsillectomy is a common surgical procedure that requires specific postoperative care to minimize complications and accelerate patient recovery. During the immediate postoperative period, nursing interventions play a crucial role in pain management, prevention of bleeding, and monitoring for signs of complications. Objective: To analyze nursing interventions for immediate postoperative tonsillectomy patients through a systematic review. Methods: A systematic review based on PRISMA methodology was carried out. The collection of information was carried out in academic databases. It was selected scientific articles, books, reports and theses published in Spanish and English among 2021 and the present time, with free access. Letters to the editor and clinical trials were excluded. The search was performed, using key terms related to tonsillectomy nursing interventions, applying language and document type filters. The most relevant data were extracted and analyzed, making a qualitative synthesis of the information obtained. Results and discussion: It was identified that the main nursing interventions in the immediate postoperative period of tonsillectomy include constant monitoring of vital signs, assessment of pain and adequate administration of analgesia to improve patient comfort. Adequate hydration and prevention of nausea and vomiting are also key to avoiding complications. Nurses play an essential role in the postoperative care of patients undergoing tonsillectomy, ensuring a safe recovery and minimizing risks by implementing evidence-based care.